Health and wellbeing in Norway: Population norms and the social gradient - Olsen, Jan Abel; Lindberg, Marie Hella; Lamu, Admassu Nadew (Social Science & Medicine, 2020)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Measures of health-related quality of life are important in health technology assessments, and useful when analysing health inequalities across population sub-groups. This paper provides population norms on health and wellbeing in Norway based on two waves of a comprehensive health survey: Wave 6 of The Tromsø Study conducted in 2007/08 (N = 12,981) and Wave 7 conducted in 2015/16 (N = 21,083). By use of these data, the paper aims to provide new insight on how different measures of health and wellbeing, and different indicators for socio-economic position, will affect the magnitude of a reported social gradient in health. We apply validated multi-item instruments for measuring health and subjective well-being; the health state utility instrument EQ-5D, and the satisfaction with life scale, as well as a direct valuation of health on a visual analogue scale. We apply three indicators for socio-economic position; education, occupation and household income, each measured along four levels. After descriptive statistics, regression analyses are performed separately for men and women, adjusted for age, to explain the magnitude of the social gradient along each socio-economic indicator. The social gradient in health showed a consistent positive trend, along all three socio-economic indicators; it was strongest with income, and weakest with education. When health had been valued directly on a visual analogue scale, the gradient was steeper than when valued indirectly via the EQ-5D descriptive system. The social gradient in subjective well-being also showed consistent positive trends, except with education as the socio-economic indicator. We have shown that the magnitude of the social gradient critically depends on which socio-economic indicator is used, and whether health is being measured indirectly via the EQ-5D descriptive system or directly on a visual analogue scale. The strongest gradient in subjective well-being was observed with income as the socio-economic ...